Radiation hazard indices in the application of phosphogypsum mixtures as a building material: proposal for a Brazilian regulation (Brazilian Journal of Radiation Sciences, 2019)
Phosphogypsum (PG), a by-product from the phosphoric acid industry, is being worldwide stockpiled, posing environmental problems. Viability of the PG safe re-use in civil construction has been studied, as PG can contain natural radionuclides in significant concentrations. We propose a policy for using PG as a building material, limiting the total concentration of 226Ra plus 228Ra by mixing PG with natural gypsum. It was concluded that PG from the largest Brazilian deposits could be used without any dilution, when the sum of the activity concentrations of 226Ra and 228Ra does not exceed 150 Bq kg-1. For higher values, the approach is to mix PG with increasing amounts of natural gypsum, so that the final concentration does not exceed 1000 Bq kg-1. We show that PG re-use in such a way is feasible in terms of radiological protection and recommended to minimize PG piles environmental impact
Keywords: phosphogypsum; NORM; radiation hazard index